Running from stress: a perspective on the potential benefits of exercise-induced small extracellular vesicles for individuals with major depressive disorder - Khoury, Reine; Nagy, Corina (Frontiers in Molecular Biosciences, 2023)
Aerobic exercise promotes beneficial effects in the brain including increased synaptic plasticity and neurogenesis and regulates neuroinflammation and stress response via the HPA axis. Exercise can have therapeutic effects for numerous brain-related pathologies, including major depressive disorder (MDD). Beneficial effects of aerobic exercise are thought to be mediated through the release of “exerkines” including metabolites, proteins, nucleic acids, and hormones that communicate between the brain and periphery. While the specific mechanisms underlying the positive effects of aerobic exercise on MDD have not been fully elucidated, the evidence suggests that exercise may exert a direct or indirect influence on the brain via small extracellular vesicles (sEVs), which have been shown to transport signaling molecules including “exerkines” between cells and across the blood brain barrier (BBB). sEVs are released by most cell types, found in numerous biofluids, and capable of crossing the BBB. sEVs have been associated with numerous brain-related functions including neuronal stress response, cell-cell communication, as well as those affected by exercise like synaptic plasticity and neurogenesis. In addition to known exerkines, they are loaded with other modulatory cargo such as microRNA (miRNA), an epigenetic regulator that regulates gene expression levels. How exercise-induced sEVs mediate exercise dependent improvements in MDD is unknown. Here, we perform a thorough survey of the current literature to elucidate the potential role of sEVs in the context of neurobiological changes seen with exercise and depression by summarizing studies on exercise and MDD, exercise and sEVs, and finally, sEVs as they relate to MDD. Moreover, we describe the links between peripheral sEV levels and their potential for infiltration into the brain. While literature suggests that aerobic exercise is protective against the development of mood disorders, there remains a scarcity of data on the therapeutic effects of exercise. Recent studies have shown that aerobic exercise does not appear to influence sEV size, but rather influence their concentration and cargo. These molecules have been independently implicated in numerous neuropsychiatric disorders. Taken together, these studies suggest that concentration of sEVs are increased post exercise, and they may contain specifically packaged protective cargo representing a novel therapeutic for MDD.